Longitudinal suicide ideation trajectories in a clinical trial of brief CBT for U.S. military personnel recently discharged from psychiatric hospitalization. (November 2020) - Lee, Daniel J.; Bryan, Craig J.; Rudd, M. David
Highlights: Research among adolescent samples has suggested patterns of change in suicidal ideation (SI) following psychiatric hospitalization discharge are heterogenous and predictive of subsequent suicide attempts. However, no studies have examined SI trajectories following discharge among adult samples or the effect of treatment on trajectories. We used growth mixture modeling to examine trajectories of SI among 152 active duty military personnel in a randomized controlled trial comparing brief cognitive-behavioral therapy (CBT) for suicide prevention to treatment as usual following discharge from inpatient psychiatric hospitalization for a suicide risk. Analyses of SI at baseline, 3-, 6-, and 12-months post-discharge among the full sample randomized to both conditions revealed two trajectories: rapid improvers (59.21%) and gradual improvers (40.79%). Gradual improvers were more than twice as likely to attempt suicide in the two years following discharge. Abstract: Research among adolescent samples has suggested patterns of change in suicidal ideation (SI) following psychiatric hospitalization discharge are heterogenous and predictive of subsequent suicide attempts. However, no studies have examined SI trajectories following discharge among adult samples or the effect of treatment on trajectories. We used growth mixture modeling to examine trajectories of SI among 152 active duty military personnel in a randomized controlled trial comparing brief cognitive-behavioral therapy (CBT) for suicide prevention to treatment as usual following discharge from inpatient psychiatric hospitalization for a suicide risk. Analyses of SI at baseline, 3-, 6-, and 12-months post-discharge among the full sample randomized to both conditions revealed two trajectories: rapid improvers (59.21%) and gradual improvers (40.79%). Gradual improvers were more than twice as likely to attempt suicide in the two years following discharge. Exploratory analyses suggested that, relative to those in the treatment as usual condition, those randomized to brief CBT in both trajectories may be less likely to make a suicide attempt during the follow-up period. Results replicate and extend prior research in identifying distinct ideation trajectories following psychiatric inpatient hospitalization for suicide risk to active-duty personnel in a treatment trial and linking these trajectories to suicide attempts during follow-up.